Serum trace element and heavy metal levels in patients with sepsis. (2nd July 2020) - Akkaş, İdris and Ince, Nevin and Sungur, Mehmet Ali
Abstract: Background and objectives: Sepsis is defined as a life-threatening organ dysfunction syndrome, which occurs when the body's immune response to infection is impaired. The aim of the present study was to investigate serum Iron, Copper, Zinco, Cobalt, Chromium, Selenium, Vanadium, Nickel, Cadmium, and Aliminium levels in patients with sepsis. Materials and methods: This prospective and observational study was conducted at a tertiary care university hospital of Turkey from 2015 to 2016, and comprised patients with sepsis. Serum concentrations of 10 elements were analyzed using inductively coupled plasma mass spectrometry. Analyses were performed at the laboratory of Düzce University Scientific and Technological Research Application and Research Center. A total of 87 participants (52 men, 35 women; average age, 74.11 ± 14.26) were enrolled. Results: When evaluated in terms of trace elements, a significant difference was noted between the sepsis and control groups in terms of the levels of the five elements. Chromium, Iron, Nickel, Copper, and Cadmium levels were significantly higher in the sepsis group. Conclusion: Our study indicated in particular, Iron, Copper, Chromium, Nickel, and Cadmium levels were elevated in patients with sepsis.